WHAT FACTORS AFFECT BUNDLE ADOPTION IN A VOLUNTARY QUALITY IMPROVEMENT CAMPAIGN?: AN ASSESSMENT OF PROJECT JOINTS. Issue 4 (17th March 2014) - Khodyakov, Dmitry; Susan Ridgely, M; Huang, Christina; Sorbero, Melony E; Schneider, Eric C
Abstract : Introduction: While innovative strategies have been used to accelerate the spread of complex, evidence-based practices, few have been rigorously evaluated. Project JOINTS is a national QI campaign in the U.S. undertaken by the Institute for Healthcare Improvement to spread evidence-based practices to prevent surgical site infection (SSI) after hip and knee arthroplasty. Building on social network theory, Project JOINTS was designed to activate a "rapid spread network" (RSN) of state-level organizations ("nodes") to help disseminate an enhanced SSI prevention bundle. An evaluation by the RAND Corporation aimed to (a) describe the RSN and the role of nodes, and (b) determine whether campaign engagement affects the uptake of a bundle of evidence-based practices. Methods: After the 6–month intervention period, RAND conducted telephone interviews to measure node and hospital engagement with Project JOINTS, hospital adherence to QI methods, and hospital bundle uptake. We interviewed representatives of node organizations in nine out of ten states participating in Project JOINTS. We also interviewed representatives of 73 of the 109 participating Project JOINTS hospitals (67% participation rate) in five of the states. Thematic analysis was used to describe the RSN; logistic and OLS regression models were used to evaluate the impact of hospital engagement and adherence to QI methods on bundle uptake. Results: Qualitative results show that nodes helped recruit hospitals and disseminate campaign information. Quantitative findings suggest that complete bundle uptake was positively associated with both adherence to the QI methods and hospital engagement. Initiation of and improved adherence to individual bundle components was positively associated only with hospital engagement, and especially with the use of project materials and tools. Discussion: Our qualitative results illustrate the important role nodes play in helping IHI recruit hospitals and disseminating campaign information, thereby serving as trust brokers. While nodes may be a necessary component of a successful QI campaign, campaign organizers may also need to reach out to hospitals directly, or ask their nodes to more actively encourage hospitals to use campaign resources and participate in campaign activities, to facilitate intervention uptake. Our quantitative results further support QI campaigns as a means of increasing adoption of evidence-based patient safety bundles in orthopedic practice and stress the importance of relying on QI methods and actively engaging hospitals. Declaration of competing interests: This study was funded by a demonstration and evaluation grant (1 R18 AE000051) awarded to the Institute for Healthcare Improvement and the RAND Corporation by the U.S. Department of Health and Human Services, Office of the Assistant Secretary for Planning and Evaluation. All authors report no competing interests.